Covid-19 and financial hardship in London - Diego Collado; Daria Popova; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
Using UKMOD, the UK tax-benefit microsimulation model, we analyse the impact on Londoners of the Covid-19 crisis, of the emergency policies put in place since March 2020 and of some counterfactual policy options, including the continuation of the 20 weekly uplift in Universal Credit and Working Tax Credit. Our main results can be summarised as follows: 1) The emergency measures introduced by the Government in March 2020 proved very effective at protecting the incomes of Londoners, particularly some of the most disadvantaged groups. 2) Withdrawing the 20 a week uplift to Universal Credit and Working Tax credits will put 130,000 more Londoners in poverty, with some of the most disadvantaged groups, including 60,000 lone parents, being disproportionately affected. The number of Black Londoners living in poverty would grow by 8% compared to 6% for all ethnic groups. 3) Less well-off Londoners will be worst affected, with the poorest 10% experiencing an 8% decrease in their incomes. 4) While Londoners will be more affected than the rest of the country by the withdrawal of the 20 uplift; across the UK, the poorest 10% of people will see their incomes cut by 5%. 5) On the other hand, keeping the 20 a week uplift to Universal Credit and Working Tax credits and going further by removing all the Benefit Caps would cut child poverty in London by 10%, keeping more than 70,000 children out of poverty.
Keywords: 330; Health; Income Dynamics; Lone Parents; Microsimulation; Household Economics; Poverty; Covid-19; Taxation; Welfare Benefits; Public Policy; Economic Policy; Ethnic Groups